2016
DOI: 10.1093/jpepsy/jsw004
|View full text |Cite
|
Sign up to set email alerts
|

Parent Perceptions of Illness Uncertainty and Child Depressive Symptoms in Juvenile Rheumatic Diseases: Examining Caregiver Demand and Parent Distress as Mediators

Abstract: Results highlight the role of illness appraisals in adjustment to juvenile rheumatic diseases, and provide preliminary evidence that parent appraisals of illness uncertainty impact parent distress and child depressive symptoms indirectly through increased perceptions of caregiver demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
2
26
1
2
Order By: Relevance
“…The concept of 'illness uncertainty' has been explored both in acute and chronic illnesses [14,15] and Mishel has defined it as the inability to determine the meaning of illness related events [16]. The influence of illness uncertainty has been examined in lifethreatening conditions such as cancer [17][18][19][20], cardiopulmonary conditions [21,22] and HIV [23,24] and is found to be an additional psychosocial stressor on patients [25] and families [26]. Individuals living with SCD and their families may also experience uncertainty in everyday life due to the unpredictability of onset of a painful crisis and unforeseen complications, such as infections or the fear of early death.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of 'illness uncertainty' has been explored both in acute and chronic illnesses [14,15] and Mishel has defined it as the inability to determine the meaning of illness related events [16]. The influence of illness uncertainty has been examined in lifethreatening conditions such as cancer [17][18][19][20], cardiopulmonary conditions [21,22] and HIV [23,24] and is found to be an additional psychosocial stressor on patients [25] and families [26]. Individuals living with SCD and their families may also experience uncertainty in everyday life due to the unpredictability of onset of a painful crisis and unforeseen complications, such as infections or the fear of early death.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual framework of “uncertainty in illness” was found to be helpful for interpreting the data although it was not used to develop the study or its methods (Mishel, ; Mishel, ). That is, uncertainty is described as the inability to determine the meaning of illness‐related events and may be related to distress or confusion (Chaney, Gamwell, Baraldi, et al, ; Eisenberg et al, ; Sajjadi, Rassouli, Abbaszadeh, Brant, & Majd, ). These mothers apparently preferred to use emotional coping, by avoiding detailed explanations to their young children and avoiding more research for more medical information about the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple areas have been described as affected in caregivers of patients with JIA, some of those appeared during the descriptive analysis of the population. In other studies, changes were reported in relationships and role distribution in families, emotional distress experiences, appraisal of illness uncertainty, elevated out-of-pocket costs and limited time for other activities [10,13,14,28,[32][33][34]. Results also show that caregivers often avoid to reveal their emotions to other family members [13,14,35].…”
Section: Discusionmentioning
confidence: 75%